Pengaruh Prenatal Yoga Terhadap Penurunan Nyeri Pinggang pada Ibu Hamil Trimester III di TPMB Umi Banjarbaru - Hadijah, Siti; Zakiah; Laili, Fitria Jannatul; Kirana, Rita (Bunda Edu-Midwifery Journal (BEMJ), 2026)
Introduction: Lower back pain is a common complaint experienced by pregnant women, especially in the third trimester. Based on a preliminary study conducted at TPMB Umi Banjarbaru, 7 out of 10 pregnant women (70%) complained of back pain during the third trimester of pregnancy. Prenatal yoga can reduce complaints experienced by pregnant women during the third trimester, one of which was low back pain. The aim of this study was to analyze the effect of prenatal yoga on reducing low back pain in pregnant women in the third trimester at TPMB Umi Banjarbaru. Methods: This research was an analytical study with a pre-experimental method with a pre-test post-test one group design approach. The population consisted of 30 respondents, taken using the Purposive sampling technique. The independent variable was prenatal yoga, the dependent variable was low back pain in pregnant women in the third trimester. Data collection used a back pain scale score sheet visual analogue scale. Data were analyzed used the Wilcoxon Signed Rank test with a significance of (α) is 0.05. Result: There was an effect of prenatal yoga on reducing low back pain in pregnant women in the third trimester at TPMB Umi Banjarbaru (p-value was 0.001). Conclusion: There was a significant effect of prenatal yoga on reducing low back pain in pregnant women. The more regularly participate in prenatal yoga, the less low back pain will decrease. It is hoped that pregnant women are encouraged to participate in prenatal yoga regularly to minimize symptoms during pregnancy and prepare for a comfortable giving birth.